Understanding victims and restorative justice - Dignan, James (Crime and justice., 2005)
This new book examines the origins of and the relationship between the rise of the "victim movement" and the emergence of "restorative justice." It assesses their strengths and weaknesses in meeting the needs of victims as part of the overall response to crime. It is for students from a range of disciplines including criminology, sociology, and law, and for professionals, practitioners, and policy makers working within the criminal justice system.